Design and discovery of a highly potent ultralong-acting GLP-1 and glucagon co-agonist for attenuating renal fibrosis - Qian Zhao; Jiale Dong; Han Liu; Hui Chen; Huan Yu; Shuyin Ye; Shuangjin Yu; Yu Li; Longhui Qiu; Nazi Song; Hongjiao Xu; Qi Liu; et al. (Elsevier, 2024)
The role of co-agonists of glucagon-like peptide-1 receptor (GLP-1R) and glucagon receptor (GCGR) in chronic kidney disease (CKD) remains unclear. Herein we found that GLP-1R and GCGR expression levels were lower in the kidneys of mice with CKD compared to healthy mice and were correlated with disease severity. Interestingly, GLP-1R or GCGR knockdown aggravated the progression of kidney injury in both diabetic db/db mice and non-diabetic mice undergoing unilateral ureteral obstruction (UUO). Based on the importance of GLP-1R and GCGR in CKD, we reported a novel monomeric peptide, 1907-B, with dual-agonism on both GLP-1R and GCGR. The data confirmed that 1907-B had a longer half-life than long-acting semaglutide in rats or cynomolgus monkeys (∼2-3 fold) and exhibited better therapeutic contribution to CKD than best-in-class monoagonists, semaglutide, or glucagon, in db/db mice and UUO mice. Various lock-of-function models, including selective pharmacological activation and genetic knockdown, confirmed that 1907-B's effects on ameliorating diabetic nephropathy in db/db mice, as well as inhibiting kidney fibrosis in UUO mice, were mediated through GLP-1 and glucagon signaling. These findings highlight that 1907-B, a novel GLP-1R and GCGR co-agonist, exerts multifactorial improvement in kidney injuries and is an effective and promising therapeutic option for CKD treatment.